Fostering Literacy Culture: An In-depth Exploration of the Reading Corner Initiative at Madrasah Ibtidaiyah Nyatnyono 01 Semarang Regency - Cahyaningsih, Esty; Khoiruddin Nasution (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study delves into the enhancement of literacy culture at Madrasah Ibtidaiyah Nyatnyono 01, Semarang Regency, through Talcott Parsons' functional-structural theory, particularly the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency), using a qualitative case study method. Structured interviews with key personnel like Mrs. AL, the head of the Madrasah, participatory observation, and documentation analysis formed the basis of data collection, which was analyzed through the Miles and Huberman model for structured and reliable insights. The research facilitated by the Reading Corner initiative highlights significant improvements in literacy among students. Adaptation was evident as students actively engaged in reading activities during breaks, while Goal Attainment was reflected in integrating literacy into various subjects, aiming for improved academic performance. Integration was achieved by blending literacy with diverse issues using innovative teaching models and motivational materials, and Latency was seen in the internalization of literacy habits within the school community. Despite its specific focus and the need for further research to explore long-term impacts in varied contexts, this study contributes to the broader discourse on literacy, emphasizing the need for culturally specific approaches in educational settings and providing a potential model for enhancing literacy culture in other institutions.